Procurement Planning and Contract Performance in Local Government Case of Mbale District Local Government - Jackline Namakoye (Uganda Christian University, 2024)
This research report was undertaken to examine procurement planning and contract performance in local governments. It was guided by three objectives; to find out the effect of supplier management on contract performance in Mbale district local government, to assess the effect of risk management on contract performance in Mbale district local government, to determine the effect of supplier selection on contract performance in Mbale district local government. The researcher used a sample size of 45 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that supplier management has a significant effect on contract performance in Mbale district local government. Supported by the following responses; 80% were positive to the statement that the goal is to ensure that suppliers meet the buyer's expectations in terms of quality; 66.6% who were also the majority were positive to the statement that there is an improved relationship with suppliers; 62.3% who also constituted the majority were positive to the statement that the entity is in position to identify inefficient and unreliable suppliers quickly. Results of the second objective revealed that risk management has a significant effect on contract performance in Mbale district local government. Supported by the following responses; 66.7% of the respondents were positive to the statement that the team remains focused, 66.6% forming the majority were positive to the statement that there's better quality data for decision making, it can be observed that 64.5% were positive to the statement that budgets rely less on guesswork. Results of the third objective showed that supplier selection has a significant effect on contract performance in Mbale district local government. 73.4% forming the majority were positive to the statement that respondents maximize overall value to the purchaser, 51.1% were positive to the statement that respondents develop closeness and long-term relationships between buyers and suppliers. Superiors should be proactive by addressing issues, challenges and problems as they arrive prevents them from festering into something more serious that is to say early and frank discussion and action that build trust and respect, regularly review the deliverables and performance where every contract manager wants to know that they are receiving the service they need and to the standard they expect.
Undergraduate Research